2021
DOI: 10.1155/2021/8066133
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasonic Elastography Combined with Human Papilloma Virus Detection Based on Intelligent Denoising Algorithm in Diagnosis of Cervical Intraepithelial Neoplasia

Abstract: The aim of this research was to study the application of ultrasonic elastography combined with human papilloma virus (HPV) detection based on bilateral filter intelligent denoising algorithm in the diagnosis of cervical intraepithelial neoplasia (CIN) and provide a theoretical basis for clinical diagnosis and treatment of CIN. In this study, 100 patients with cervical lesions were selected as research objects and randomly divided into control group and experimental group, with 50 cases in each group. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The results showed that the AI algorithm can improve the accuracy of ultrasonic image in disease diagnosis and has good application value. Sun et al (2021) [ 24 ] concluded that the bilateral filtering intelligent denoising algorithm can improve the diagnostic value of ultrasound elastography for cervical intraepithelial neoplasia (CIN). Luo et al (2021) [ 25 ] also reached a consistent conclusion and gave certain support to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the AI algorithm can improve the accuracy of ultrasonic image in disease diagnosis and has good application value. Sun et al (2021) [ 24 ] concluded that the bilateral filtering intelligent denoising algorithm can improve the diagnostic value of ultrasound elastography for cervical intraepithelial neoplasia (CIN). Luo et al (2021) [ 25 ] also reached a consistent conclusion and gave certain support to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al introduced a denoising algorithm for an intelligent bilateral filter, which has improved image quality when used in applications. Combined with human papillomavirus (HPV) testing to diagnose CIN, the results showed that the accuracy, sensitivity, and specificity of this new technology were 95%, 95%, and 98%, respectively [ 55 ]. In summary, the bilateral filter intelligent denoising algorithm has a good denoising effect on ultrasonic elastography.…”
Section: Cervical Tumorsmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%